A NEW LYCOPOD, NOVGORODENDRON CONOPHORUM GEN. ET SP. NOV., FROM THE LOWER CARBONIFEROUS OF THE MOSCOW SYNECLISE - Gordenko N.V.; Orlova O.A.; Snigirevsky S.M. (My University, 2006)
A new lycopod, Novgorodendron conophorum gen. et sp. nov., is described from the Upper Visean deposits of the Kamenka River, near the town of Borovichi (Novgorod Region). The morphology of the leaf cushions of the new plant implies its intermediate position between the families Sublepidodendraceae Chaloner et Boureau and Lepidodendraceae Endlicher. The bases of the leaf cushions have peculiar conical appendages, a previously unknown morphological feature not recorded from other lycopods. We propose the term basal conical appendages for them. The interpretation of some epidermal elements in the leaf cushions of the Lepidodendraceae is revised. The structures of the leaf cushions that were previously treated as either stomata or cells with cystoliths are shown to be sunken multicellular trichomes. © Pleiades Publishing, Inc. 2006.
Keywords: EPIDERMAL ELEMENTS; LEAF CUSHIONS; LYCOPODS; VISEAN; Paleozoic::Carboniferous::Mississippian::Middle::Visean; Палеозой::Каменноугольная::Средний::Визейский